pH- Modified Solid Dispersions of Cefdinir for Dissolution Rate Enhancement: Formulation and Characterization - Al Nuss, Raghad; El-Zein, Hind (Journal of Pharmacy and Nutrition Sciences, 2021)
Objective: Cefdinir is a poorly- water-soluble drug, it belongs to Biopharmaceutical Classification System class IV, which shows that it may have limited therapeutic effects due to its low solubility and poor bioavailability. The aim of the present work was to design a pH-modified solid dispersion (pHM-SD) that can improve the dissolution rate of cefdinir and subsequently its bioavailability. Materials and Methods: pHM-SDs of cefdinir were prepared at different drug-to-carrier ratios by the spray-drying technique. The solid dispersions were investigated by dissolution studies at different pH media, drug release kinetics were studied, and their solid-state characterizations were performed by FTIR spectrophotometer, Scanning electron microscopy (SEM), Differential scanning calorimetry (DSC), and Powder X-ray diffraction (PXRD). Results: PVP- based and HPMC- based pHM-SDs exhibited a marked improvement in the dissolution behavior when compared with crystalline cefdinir powder, whereas Eudragit L100-based pHM-SDs showed lower dissolution at pH 1.2 and 4.5. FTIR results may indicate a formation of a salt between cefdinir and the alkalizer. Solid-state characterization may indicate a change in crystallinity of cefdinir into an amorphous state. Mathematical modeling of in vitro dissolution data indicated the best fitting with Korsmeyer–Peppas model and the drug release kinetics primarily as Fickian diffusion. Conclusion: According to these observations, pHM-SD in the presence of an alkalizer for a poorly water-soluble acidic drug, cefdinir, appeared to be efficacious for enhancing its dissolution rate.